2017
DOI: 10.1155/2017/8721240
|View full text |Cite
|
Sign up to set email alerts
|

For Better or Worse: The Effect of Prismatic Adaptation on Auditory Neglect

Abstract: Patients with auditory neglect attend less to auditory stimuli on their left and/or make systematic directional errors when indicating sound positions. Rightward prismatic adaptation (R-PA) was repeatedly shown to alleviate symptoms of visuospatial neglect and once to restore partially spatial bias in dichotic listening. It is currently unknown whether R-PA affects only this ear-related symptom or also other aspects of auditory neglect. We have investigated the effect of R-PA on left ear extinction in dichotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…Network science analysis of connectivity matrices revealed here a decrease of connectivity strength and of local efficacy within VAN and in particular in its anterior part, indicative of a decrease of modularity. The decrease in resting state connectivity coincides with the emergence of ipsilateral visual and auditory spatial representation within the left inferior parietal lobule [49,50]. The decrease in local efficiency within VAN, which we describe here, is indicative of a loss of modularity within VAN and may be instrumental in bringing up the new spatial representation.…”
Section: Plos Onesupporting
confidence: 53%
See 3 more Smart Citations
“…Network science analysis of connectivity matrices revealed here a decrease of connectivity strength and of local efficacy within VAN and in particular in its anterior part, indicative of a decrease of modularity. The decrease in resting state connectivity coincides with the emergence of ipsilateral visual and auditory spatial representation within the left inferior parietal lobule [49,50]. The decrease in local efficiency within VAN, which we describe here, is indicative of a loss of modularity within VAN and may be instrumental in bringing up the new spatial representation.…”
Section: Plos Onesupporting
confidence: 53%
“…alleviate neglect symptoms [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]64], predominantly in patients with anterior lesions in whom the posterior part of the corpus callosum and the right DAN are spared [50,65,66]. Activation studies have demonstrated that R-PA induces in neglect patients a shift of dominance by establishing ipsilateral spatial representation within VAN on the left side [30] and that it increases responsiveness of DAN [32].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…This model of neglect recovery predicts that only patients with preserved dorsal attentional system and preserved posterior callosal pathway will benefit from the shift in hemispheric dominance and hence respond to the treatment. This prediction has been validated in three independent studies 21–23…”
Section: Impact Of Cognitive Models On Stroke Rehabilitationmentioning
confidence: 83%